Deciphering the microbial communities in ticks of Inner Mongolia: ecological determinants and pathogen profiles - Chunfu Li; Rui Ma; Ai Gao; Na Jiang; Chunli Sang; Yanli Zhang; Haoqiang Tian; Jian Li; Wei Hu; Xinyu Feng (Parasites & Vectors)
Abstract Background Ticks are vectors of numerous pathogens, with their bacterial composition, abundance, diversity, and interaction influencing both their growth and disease transmission efficiency. Despite the abundance of ticks in Inner Mongolia, China, comprehensive data on their microbial communities are lacking. This study aims to analyze the microbial communities within ticks from Inner Mongolia to inform innovative control strategies for interrupting pathogen transmission. Methods Tick samples were collected from animals and vegetation in multiple locations across Inner Mongolia and stored at − 80 °C. Ticks were identified using morphological keys and molecular biology methods. Full-length 16S rRNA gene sequencing was performed on collected samples. Bacterial community composition and diversity were mainly analyzed using bioinformatic tools such as QIIME, phyloseq, and DESeq2. Alpha diversity was assessed using Chao1, ACE, and Shannon indices, while beta diversity was evaluated using Bray-Curtis dissimilarity matrices. LEfSe analysis was applied to identify taxa associated with ecological and biological variables. Results A total of 5,048,137 high-quality read counts were obtained, forming an average of 789.3 OTUs per sample. Proteobacteria, Firmicutes, and Bacteroidetes were the most dominant phyla. Bacterial community composition varied significantly with geography, with Dermacentor nuttalli showing a higher abundance of Rickettsia in Xilingol League, while other regions had different dominant genera. The microbial community also differed based on the feeding status of ticks. Additionally, the microbiota of engorged ticks showed organ specificity. Pathogen detection efforts revealed the presence of nine pathogens across all three tick species. D. nuttalli was found to carry a significantly higher burden of pathogenic bacteria, making it the most potentially threatening tick species in Inner Mongolia. Conclusions The study highlights significant variations in tick microbiomes influenced by geographic location, feeding status, and tick species. It underscores the importance of enhancing tick and tick-borne disease surveillance in Inner Mongolia for early detection and control of emerging pathogens. Graphical Abstract